High-Rise Pigs - Ang, Siew Ching (Taideyliopiston Kuvataideakatemia, 2024)
This thesis project consists of the artistic component and a written component. Both components are attempts to think through my object of fascination — the industrial pig. The artistic component, presented in Kuvan Kevät 2024, consists of two works. The first work is High-Rise Pigs, a 32-minute essay film. The second work is On Enclosures, a series of three monoprints. The written component of this thesis consists of two main parts. The first part documents this thesis, discusses the motivations behind the artistic component and ends with a reflection on the process of essaying throughout these two years. The second part, in the spirit of essaying, is a new essay on how the combination of architecture and pig might hold creative possibilities.
Keywords: fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|